(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to show the change in foreign currency rates in the specializations of foreign companies and its impact on finances, by identifying the financial and tax impact and any application of the International Accounting Standard No. (21) IAS in Iraq and multinational companies to show and audit the applications and differences that arise when starting to write International Accounting Standard No. (21) IAS IAS The research included the presentation and analysis of the financial statements of the branch of the Italian joint-stock company (X) / Iraq branch, which is a company specialized in providing engineering, consulting, construction and maintenance services in the oil, gas and energy sector. The research reached a set of conclusions and recommendations, the most important of which is that the financial statements prepared by the research sample company that provides engineering, consulting, construction and maintenance services in the oil, gas and energy sector It does not express the effects of changes in foreign currency prices. The most important recommendations are that the accounting treatments for foreign currency exchange rates are in accordance with International Accounting Standards (21-8) and the preparation of financial statements according to Standard No. (1) “Presentation of Financial Statements” and the effect on the result of the activity and on taxable income.